ANALISIS PEMERIKSAAN PAJAK DALAM MENINGKATKAN PENERIMAAN PPH PASAL 25 DI KANTOR PELAYANAN PAJAK PRATAMA MEDAN BARAT - Saragih, Joana L.; Sihotang, Lilis Karlina (UNIKA Santo Thomas, 2024)
The purpose of this study was to determine how the tax audit in increasing tax revenue of ITA 25 at KPP Pratama Medan Barat. This research uses qualitative methods. Data collection is done by interview and documentation techniques. The techniques used in this research include descriptive analysis where existing data will be collected and grouped and then analyzed. The results of this research show that the tax revenue of KPP Pratama Medan Barat has decreased and has not reached the specified target. The causes of not achieving the revenue target for the implementation of tax audits at the KPP Pratama Medan Barat are due to uncooperative taxpayers, lack of understanding of taxpayers, limited inspection teams